The violence of uncertainty: theorizing everyday immigrant necropolitics across three cases - Breanne Grace; John Doering-White; Benjamin Roth (Comparative Migration Studies)
Abstract This article theorizes everyday forms of uncertainty that immigrant and refugee populations negotiate as a form of violence. We argue that while the state has made immigrants and refugees an explicit target on which to exercise sovereignty through detention and deportation, sovereignty also operates through a necropolitics of uncertainty where immigrants and refugees face inconsistent and spatially diffuse states of exception that target their material, social, and psychological wellbeing. To support this argument, we draw on three case studies that illustrate how avoiding or opting out of social services and health care, or by “self-deporting,” are effects of targeted violence.